What happened on Beale Street - Ellis, Mary, 1951- (Ellis, Mary, 1951- Secrets of the South mysteries, 2016)
A cryptic plea from a childhood friend sends Nate and Nicki Price from New Orleans to Memphis. They find signs of a struggle at Danny Andre's address-- and signs of a lifestyle not in keeping with the choirboy they fondly remember. Danny's sister, Isabelle, accepts their help reluctantly. Together they must rely on their faith-- and get beyond painful memories.